Knowledge of Type II Diabetic Patients About Their Diabetes: A Systematic Review and Meta-Analysis - Zahedi, Mona; Dehvan, Fazel; N. Albatineh, Ahmed; Ghanei Gheshlagh, Reza (Advances in Nursing & Midwifery, 2020)
Introduction: Knowledge is the critical component to counter the harmful side-effects of chronic diseases. Diabetic patients can manage their disease based on their diabetes knowledge and following good self-care behavior. Various studies about patients' knowledge of diabetes show different results. The purpose of this study is to estimate the overall knowledge score of Iranian patients about diabetes. Methods: In the current study, ten papers published by September 2018 were identified without time limitation. A literature search for the papers was conducted using the keywords: Iran, diabetes, knowledge, and their combinations. The necessary data were extracted and analyzed through meta-analysis using the random-effects model. The I2 statistic was used to measure the heterogeneity among the studies. The data were analyzed using Stata software (Version 11). Results: The pooled estimate of the knowledge score of type II diabetes patients about their diabetes was 64% (95% CI: 52%-76%). According to the meta-regression results, there was no relationship between the knowledge score with age (P = 0.487), duration of disease (P = 0.406), and the sample size (P = 0.146). The patients' knowledge score had experienced an uptrend between 2004 and 2017, the years at which the oldest and the most recent articles were published (P = 0.06). Conclusions: Iranian patients' knowledge about their diabetes was at an average level. Education, along with medication, can significantly reduce short and long-term complications of diabetes.